ELECTRON ELECTRON INTERACTIONS IN EXPANDED-METAL COMPOUNDS - Stacy, A; Edwards, P; Sienko, M (1982)
Magnetic studies by the Faraday method were carried out over the range 4.2-200K on a variety of structures in which lithium metal was progressively "expanded." At one extreme is tetrakisammonialithium(zero), Li(NH3)4, which is Pauli metallic; at the other is monolithium [2.1.1] cryptate electride, the magnetic behavior of which is clearly nonmetallic. Intermediate, apparently just on the nonmetallic side of the metal-nonmetal transition, is the solid tetrakismethylaminelithium(zero), Li(CH3NH2)4. The electronic behavior of these "expanded-metal" compounds is interpreted in terms of Hubbard bands and Mott-Anderson transitions. The dielectric constant of the host matrix is crucial for scaling the onset of metallic behavior. © 1982.